Everyday life in the “glitzy” city: navigating belonging and exclusion in Dubai - AlMutawa, R (2021)
In this thesis, I argue that the dominant discourse on Dubai and other spectacular cities implicitly or explicitly seeks to uncover the “real” city that lies beneath the veneer of the spectacle. In doing so, the existing scholarship advances a problematic binary discourse about supposedly “authentic, local” spaces contrasted with alienating, “tourist” spaces. In these narratives, Dubai’s inhabitants are often depicted as estranged from the spectacular city, eliding the meanings that inhabitants create in it. Through an urban ethnography conducted between 2017-2019 with middle-class citizens and long-term residents in Dubai, I focus on experiences of belonging and un-belonging and show that the city is a site of complex attachments for its inhabitants. I show that my middle-class interlocutors have ambivalent, complex, and contradictory relationships with the city’s spectacles: they experience belonging, have cherished memories, and engage in cultural contestations within the spectacular urban landscapes. However, they also experience loss, rapid changes and other forms of un-belonging. This research begins by investigating how different actors implicitly or explicitly engage with discourses of authenticity about Dubai. It then explores experiences of belonging and exclusion at the intersections of ethnicity, class, gender and citizenship.